THE IMPORTANCE OF FORMING SPIRITUAL EDUCATION IN STUDENTS DURING THE THIRD RENAISSANCE PERIOD (American Journal of Pedagogical and Educational Research, 2023)
In this article, the researches on the development of moral education, methods and forms of educating young people, the analysis of many works written in the educational and moral direction of the field of education in historical sources, instilling their content and essence into young people, personality the directions of decision-making from the point of view of quality have been determined.